Perlindungan Hukum Terhadap Anak Korban Eksploitasi Seksual Komersial Melalui Media Sosial - Mutiara Nastya Rizky; Risma Intan Fitriani; Muhammad Wahyu Sudibyo; Fatma Ayu Husnasari; Firmansyah Maulana (Media Iuris, 2019)
Today, the crime rate is increasing, one of the trigger is due to the advances in the field of technology and information. Thus not a few people who use technological advances as a crime media to make money. Most of them use children as objects because children are easily persuaded and seduced to get something. One example of a crime that uses a child as an object is a sexual crime. These children are exploited as sexual disseminators disseminated through social media. Looking at the children's point of view as a weak individual then in Indonesia Law number 35 of 2014 was born to ensure that children can grow and develop optimally. So the law is regulated in detail about the rights of children and protection of children as victims of crime. On the other hand, there are several laws that regulate sexual crimes whether committed in cyberspace or not. Because of the importance of providing protection to children, there is more than one rule of law to protect children as victims of sexual crimes through social media. So the systematic specialist principle should be applied to provide legal certainty against the children. The purpose of this research was to determine the legal protection of children as victims of sexual exploitation through social media and the application of lex specialist systematic principles in the case of children as victims of sexual abuse through social media. To be able to answer existing legal problems, the research method is used with the type of doctrinal research and statute approach and conceptual approach. From this research, it can be obtained the results that in the application of the lex systematic specialist principle is based on case.